A novel, eco-friendly multi-walled carbon nanotubes functionalized copper metal-organic framework for ultrasensitive potentiometric detection of cadmium ions. Issue 6 (December 2021) - Singh, Sima; Numan, Arshid; Somaily, H.H.; Dawsari, Mona M.A.; Alqarni, Mohammed Hamed Saeed; Alam, Aftab; Kumar, Piyush
Abstract: Designing a simple and on-site detection technique for Cd 2+ is highly demanding. In the current study, an electrochemical sensor based on multi-walled carbon nanotubes (CNTs) and copper metal-organic framework (Cu-MOF) was synthesized via one-pot hydrothermal reaction for the rapid and economical monitoring of the Cd 2+ level. The structure, morphology and physical properties of prepared CNT-Cu-MOF were characterized by different physicochemical techniques. The surface of the glassy carbon electrode was modified with CNT-Cu-MOF to detect Cd 2+ in 01 M phosphate Buffer. The detection limit was found to be 0.275 nM (S/N = 3), with linear calibration curves ranging from 0.2 to 10 μM. Furthermore, the developed electrochemical sensor demonstrated excellent selectivity, stability, and repeatability. The recovery of the CNT-Cu-MOF is found to be 100.4% in a real-time sample of tap-water. The well-designed sensor employs a promising approach for on-site monitoring of Cd 2+ in tap water. Graphical Abstract: ga1 Highlights: A porous nanocomposite of CNT-Cu-MOF was synthesised and characterized for structure, morphology and physical properties. The electrochemically determined LOD was found near 0.275 nM (S/N=3) with linear calibration curves range from 0.2–10 μM. The new sensor shows excellent sensitivity, stability, and analytical precision.